Validity and Reliability of the Scale, Role Taking in Caregivers of People with Chronic Disease, ROL (2018)
ABSTRACT: Background: To determine face, content, and construct validity, and internal consistency of ROL scale. Methods and Findings: A three-phase study was conducted. First, content analysis of the scale was carried out consulting 10 professional experts. Then, face validity was analyzed with 60 caregivers. Finally, construct validity was evaluated by performing an exploratory factor analysis (EFA) with 110 participants. Internal consistency of ROL scale was also assessed. Face validity of ROL scale reached a high acceptance index in three dimensions: role performance (0.97), role organization (0.98), and response to the role (0.98). Content validity showed coherence, clarity, and relevance of the scale. From factor analysis, three components emerged and were grouped in the same manner for varimax, quartimax, and equimax rotations. Cronbach's alpha was 0.816, which is an acceptable overall value. Conclusion: ROL scale makes objective the concept of role taking in family caregivers of people with chronic disease. It demonstrated to have acceptable reliability, and construct, face, and content validity to be used in the Colombian context.